Peningkatan Soft Skill Mahasiswa Melalui Pendidikan Magang Kewirausahaan - Supri Wahyudi Utomo; Elva Nuraina; Parji Parji (Jurnal Pendidikan, 2009)
The objectives of entrepreneur apprenticeship education of the students of IKIP PGRI Madiun are: 1) to develop the students achievement in softskill/technology, work and entrepreneurship experience; 2) to motivate students to become entrepreneurs; 3) to enable students to get practical experience; and 4) to establish partnership between IKIP PGRI Madiun and PKPRI Madiun Municipality.             Output targets of the apprenticeship are: 1) the participants obtain the skill for managing business, 2) 50% of the participants can arrange business plan, 3) the participants master marketting management, 4) it establishes the healthy partenership between IKIP PGRI Madiun and PKPRI Madiun Municipality.             The specific success criterion shows that all 8 participants are able to arrange business plan. The indicator of apprenticeship success  can not be recently measured because of their being of part-timer business conduct.